2005
DOI: 10.1128/aac.49.2.619-626.2005
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Amino Acids in Human Rhinovirus 3C Protease Correlates with Broad-Spectrum Antiviral Activity of Rupintrivir, a Novel Human Rhinovirus 3C Protease Inhibitor

Abstract: The picornavirus 3C protease is required for the majority of proteolytic cleavages that occur during the viral life cycle. Comparisons of published amino acid sequences from 6 human rhinoviruses (HRV) and 20 human enteroviruses (HEV) show considerable variability in the 3C protease-coding region but strict conservation of the catalytic triad residues. Rupintrivir (formerly AG7088) is an irreversible inhibitor of HRV 3C protease with potent in vitro activity against all HRV serotypes (48 of 48), HEV strains (4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
116
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 62 publications
2
116
2
1
Order By: Relevance
“…In these latter studies, pleconaril and pirodavir demonstrated a significantly wider range in antiviral potency (1,590-to 2,707-fold range in EC 50 values) and activity against most but not all HRV serotypes tested. The comparable range in antiviral activity of Compound 1 when tested against numerous different picornaviruses is consistent with DNA sequence analyses performed on 3C protease coding gene regions, which demonstrate a significant level of homology in substrate/inhibitor binding regions (3). In mechanism of action studies, Compound 1 was also shown to inhibit the HRV 14 3C-mediated proteolytic cleavage of viral precursor polyproteins into their processed viral products, confirming that the cell-based in vitro antiviral activity of Compound 1 is due to a direct inhibition of HRV 3C protease.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In these latter studies, pleconaril and pirodavir demonstrated a significantly wider range in antiviral potency (1,590-to 2,707-fold range in EC 50 values) and activity against most but not all HRV serotypes tested. The comparable range in antiviral activity of Compound 1 when tested against numerous different picornaviruses is consistent with DNA sequence analyses performed on 3C protease coding gene regions, which demonstrate a significant level of homology in substrate/inhibitor binding regions (3). In mechanism of action studies, Compound 1 was also shown to inhibit the HRV 14 3C-mediated proteolytic cleavage of viral precursor polyproteins into their processed viral products, confirming that the cell-based in vitro antiviral activity of Compound 1 is due to a direct inhibition of HRV 3C protease.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, Compound 1 demonstrated comparable antiviral activity against all picornaviruses tested (36-fold range in EC 50 values). While this is similar to that reported for rupintrivir (3,24), it is in contrast to that reported for inhibitors that target capsid-binding, e.g., pleconaril and pirodavir (24). In these latter studies, pleconaril and pirodavir demonstrated a significantly wider range in antiviral potency (1,590-to 2,707-fold range in EC 50 values) and activity against most but not all HRV serotypes tested.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Interestingly, recent studies indicated that the inhibitor is also effective against enteroviruses (6,13,24), presumably due to the structural similarity of their 3C proteases. A recent study showed that the interferon (IFN)-mediated antiviral mechanism can be compromised by the proteolytic cleavage of EV71…”
mentioning
confidence: 99%
“…The inhibitors of the 3C protease of picornavirus, such as ruprintrivir, may potentially inhibit the norovirus protease given the overall similarity between the proteases of these viruses. (Binford et al, 2005;De Palma et al, 2008c;Leyssen et al, 2008).…”
Section: Proteasementioning
confidence: 99%